Shariah Bond as Financial Instrument For Local Government - Anim Rahmayati (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2016)
This study aims to analyse the potential of sharia bonds in the region as an alternative to local financing. This research is a kind of literary descriptive qualitative research using SWOT analysis. The results of this study indicate that in the area of sharia bonds is an alternative worth considering regional funding compared to other funding. Support policy, very large financing needs for region infrastructure development, the market potential in the area of sharia bonds is an opportunity for local governments in Indonesia to immediately issue sharia bonds in the area.DOI: 10.15408/sjie.v5i1.3126